(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Radiology informatics plays a pivotal role in modern healthcare, facilitating the efficient management and integration of diagnostic imaging data. Nurses, as frontline healthcare providers, are increasingly involved in radiology informatics initiatives, contributing to data management, patient care, and interdisciplinary collaboration. This article explores the nursing perspectives on radiology informatics, encompassing their roles, challenges, best practices, and future directions. Key topics include the understanding of radiology informatics components such as Picture Archiving and Communication Systems (PACS) and Electronic Health Records (EHR), nursing responsibilities in data management and integration, challenges such as data security and training needs, and strategies for effective implementation. Through case studies and examples, this article illustrates successful nursing-led initiatives in radiology informatics. Emphasizing the importance of ongoing education and interdisciplinary communication, it underscores the critical role of nurses in optimizing radiology informatics for improved patient outcomes and healthcare delivery.